The Effect Citric Acid Solution on Physical and Chemical Properties of Porang Flour (Amorphophallus Oncophyllus): Porang flour - Ulyarti, Ulyarti; Sahendra, Gilang; Mursyid, M (PUI BiGME Universitas Jambi, 2024)
.